Lessons Learned from Two Usability Studies of Digital Skiing Game with Elderly People in Finland and Japan - Aung Pyae; Tapani Joelsson; Teppo Saarenpää; Luimula Mika; Christina Kattimeri; Paula Pitkäkangas; Patric Granholm; Jouni Smed (Serious Games Society, 2017)
Physical decline is associated with old age. Engagement in regular physical exercises can help elderly people improve their physical functionalities, as well as cognitive abilities. Among modern technologies, digital games have the potential to promote elderly people's engagement in physical exercises through fun and enjoyable gameplay. Although commercial digital games show promise, most of them are not senior-friendly. The literature also suggests that more studies need to be undertaken to understand the usability and usefulness of digital games for elderly people. Hence, in this study, we designed and developed a digital game-based Skiing activity for elderly people. Then, we evaluated it with the Finnish and Japanese elderly participants in Finland and Japan to investigate their feedback towards the usability and usefulness of the game. The findings from both studies show that digital games are useful for promoting elderly people's engagement in physical activities. While digital games are promising to be used as an alternative solution for promoting the Japanese elderly participant's physical activities, the Finnish elderly participants recommend to use it when they don't have access to non-digital physical exercises. The lessons learned from this study can help researchers and practitioners gain insights into game design and development for elderly people and their physical activities.